Cattle Tail Lice - Phillip E. Kaufman; Philip G. Koehler; Jerry F. Butler (EDIS, 2006)
The cattle tail louse, Haematopinus quadripertusus (Figure 1), is the most important damaging cattle louse in Florida. In other parts of the United States the short-nosed cattle louse is the major pest. While much information is available for the control of short-nosed cattle lice, only limited information is available specifically on control of the tail louse. Important differences in the biology of these two species require differing control strategies. This document is ENY-271, one of a series of the Department of Entomology and Nematology, UF/IFAS Extension. Original publication date May 1995. Revised December 2005.